Genital human papillomavirus infection among patients attending an STD clinic. Issue 6 (December 1993) - Strand, A; Rylander, E; Evander, M; Wadell, G
Abstract : OBJECTIVES--To determine the prevalence of human papillomavirus (HPV) infection in patients, male and female, attending a clinic for sexually transmitted diseases (STDs). DESIGN--A randomly selected group of patients representative of the population studied and first-time visitors to the STD clinic, were asked to participate in the study. Samples from the skin and mucous membranes of the lower genital region were taken for cytological analysis by the polymerase chain reaction (PCR) method for HPV DNA. The patients then underwent colposcopy or peniscopy after acetic acid application. SETTING--Department of Dermatology and Venereology, University Hospital, Uppsala, Sweden. SUBJECTS--A total of 131 patients, 66 women and 65 men, attending the clinic for various reasons. RESULTS--At colposcopy/peniscopy, 18 patients (10 men and 8 women) had lesions typical of, and 24 (12 men and 12 women) suspicious of HPV infection. With the PCR technique HPV DNA was detected in 72% of the patients with typical lesions and in 54% of those with suspicious lesions. CONCLUSION--Nearly one-third or 30.5% of these randomly selected patients in a Swedish STD clinic were infected by HPV. The diagnosis was made by clinical inspection and/or by HPV DNA analysis with PCR.